Padlet-Based Predict Observe Explain (POE) Learning Model: Learning Outcomes of PAI and Character Education - Rosyadi Tomi; Baharudin Baharudin; M. Indra Saputra (ETDC: Indonesian Journal of Research and Educational Review, 2026)
This research is motivated by low student learning outcomes in Islamic Religious Education (PAI) and Character Building at Middle School 7 Krui, particularly in higher-order thinking skills (C5 and C6). This issue stems from monotonous teaching methods, varied student comprehension levels, limited media, and low motivation. This study aims to determine the effect of the Padlet-based Predict-Observe-Explain (POE) learning model on student learning outcomes. Using a quantitative approach with a quasi-experimental, post-test only control group design, the sample comprised two classes: an experimental class taught via the Padlet-based POE model and a control class taught conventionally. Data were collected using validated and reliable multiple-choice tests, then analyzed using normality, homogeneity, t-test, and Mann-Whitney tests. The results showed a significant difference in learning outcomes between the two groups, with a t-test significance value of 0.030 and a Mann-Whitney test value of 0.040 (p < 0.05). This indicates that the Padlet-based POE model effectively improves learning outcomes, especially in critical and analytical thinking. This success is driven by the POE syntax—prediction, observation, and explanation—integrated with interactive digital media, which enhances student activity, motivation, and comprehension. In conclusion, the Padlet-based POE learning model has a positive and significant influence on student learning outcomes. It serves as an innovative and effective alternative learning strategy for Islamic Religious Education and Character Education.